Implementación del teleférico como sistema masivo de transporte público en la ciudad de Villavicencio- Meta (2020)
The present work was carried out in order to present a hypothetical model of a cable car system that would allow the solution to the mobility problems that affect the city of Villavicencio so much, for this, everything learned during the training process was put into practice as architect at the Antonio Nariño University.